Positional role differences in the aerobic and anaerobic power of elite basketball players - Pojskic, H.; Separovic, V.; Uzicanin, E.; Muratovic, M.; Mackovic, S. (Journal of Human Kinetics, 2015)
The aim of the present study was to compare the aerobic and anaerobic power and capacity of elite male basketball players who played multiple positions. Fifty-five healthy players were divided into the following three different subsamples according to their positional role: guards (n = 22), forwards (n = 19) and centers (n = 14). The following three tests were applied to estimate their aerobic and anaerobic power and capacities: the countermovement jump (CMJ), a multistage shuttle run test and the Running-based Anaerobic Sprint Test (RAST). The obtained data were used to calculate the players` aerobic and anaerobic power and capacities. To determine the possible differences between the subjects considering their different positions on the court, one-way analysis of variance (ANOVA) with the Bonferroni post-hoc test for multiple comparisons was used. The results showed that there was a significant difference between the different groups of players in eleven out of sixteen measured variables. Guards and forwards exhibited greater aerobic and relative values of anaerobic power, allowing shorter recovery times and the ability to repeat high intensity, basketball-specific activities. Centers presented greater values of absolute anaerobic power and capacities, permitting greater force production during discrete tasks. Coaches can use these data to create more individualized strength and conditioning programs for different positional roles.